Acute respiratory infection case definitions for young children: a systematic review of community‐based epidemiologic studies in South Asia. Issue 12 (20th September 2015) - Roth, Daniel E.; Gaffey, Michelle F.; Smith‐Romero, Evelyn; Fitzpatrick, Tiffany; Morris, Shaun K.
Abstract: Objective: To explore the variability in childhood acute respiratory infection case definitions for research in low‐income settings where there is limited access to laboratory or radiologic investigations. Methods: We conducted a systematic review of community‐based, longitudinal studies in South Asia published from January 1990 to August 2013, in which childhood acute respiratory infection outcomes were reported. Case definitions were classified by their label (e.g. pneumonia, acute lower respiratory infection) and clinical content 'signatures' (array of clinical features that would be always present, conditionally present or always absent among cases). Case definition heterogeneity was primarily assessed by the number of unique case definitions overall and by label. We also compared case definition‐specific acute respiratory infection incidence rates for studies reporting incidence rates for multiple case definitions. Results: In 56 eligible studies, we found 124 acute respiratory infection case definitions. Of 90 case definitions for which clinical content was explicitly defined, 66 (73%) were unique. There was a high degree of content heterogeneity among case definitions with the same label, and some content signatures were assigned multiple labels. Within studies for which incidence rates were reported for multiple case definitions, variation in content was always associated with a change in incidence rate, even when the content differed by a single clinical feature. Conclusion: There has been a wide variability in case definition label and content combinations to define acute upper and lower respiratory infections in children in community‐based studies in South Asia over the past two decades. These inconsistencies have important implications for the synthesis and translation of knowledge regarding the prevention and treatment of childhood acute respiratory infection.